Therapeutic and Industrial Applications of Curdlan With Overview on Its Recent Patents - Chaudhari, Vinay; Buttar, Harpal Singh; Bagwe-Parab, Siddhi; Tuli, Hardeep Singh; Vora, Amisha; Kaur, Ginpreet (Frontiers in Nutrition, 2021)
Curdlan is an exopolysaccharide which is composed of glucose linked with β-1,3-glycosidic bond and is produced by bacterium such as Alcaligenes spp., Agrobacterium spp., Paenibacillus spp., Rhizobium spp.; Saccharomyces cerevisiae, Candida spp. and fungal sources like Aureobasidium pullulan, Poria cocos etc. Curdlan has been utilized in the food and pharmaceutical industries for its prebiotic, viscosifying and water-holding properties since decades. Recently, the usefulness of curdlan has been further explored by the pharmaceutical industry for its potential therapeutic applications. Curdlan has exhibited immunoregulatory and anti-tumor activity in preclinical settings. It was observed that curdlan can prevent proliferation of malarial merozoites in vivo, therefore, it may be considered as a promising therapy for the treatment of end-stage malaria. Also, curdlan has demonstrated potent antiviral effects against human immunodeficiency virus (HIV) and Aedes aegypti virus. It has been suggested that the virucidal properties of curdlans should be extended further for other deadly viruses, such as Severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and the current Severe acute respiratory coronavirus-2 syndrome (SARS-CoV-2/COVID-19). The prebiotic property of curdlan would confer beneficial effects on the host by promoting the growth of healthy microbiota in the gut, and consequently help to reduce gastrointestinal disorders. Therefore, curdlan can be employed in the manufacture of prebiotics for the management of various gastrointestinal dysbiosis problems. Studies on the mechanism of action of curdlan-induced suppression in microbial and tumour cells at the cellular and molecular levels would not only enhance our understanding regarding the therapeutic effectiveness of curdlan, but also help in the discovery of new drugs and dietary supplements. The primary focus of this review is to highlight the therapeutic interventions of curdlan as anti-cancer, anti-malaria, anti-viral and anti-bacterial agent in humans. In addition, our review provides latest information about the chemistry and biosynthesis of curdlan and its applications for making novel dairy products, functional foods and nutraceuticals as well as details about the recent patents of curdlan and its derivatives.